(untitled) (SOUTH ARAL SEA MEDICAL JOURNAL, 2025)
This article presents measures to improve oral hygiene and increase its preventive effectiveness and reduce the development of complications, taking into account the prevalence of dental diseases caused by candida, the complexity of diagnosis and treatment, and the prevalence of periodontal tissue diseases caused by this dise